Risk and protective factors for Long COVID in Brazilian adults (CUME Study) - Eduvirgem, Júlio; Bressan, Josefina; Hermsdorff, Helen Hermana Miranda; Montenegro, Livia Cozer; Brandão, Marlise Lima; Neves, Alessandra Aparecida Tavares; da Silva, Lucas Samuel Aristides; Gerake-Dias, Thiago Alexandre; Pimenta, Adriano Marçal (Frontiers in Medicine, 2024)
Background Most people recover from COVID-19, however, between 5 to 20% have experienced new, recurring, or continuous health problems four or more weeks after being infected, a phenomenon called Long COVID, and whose reasons for its manifestation are incipient. Our objective was to analyse the risk and protective factors for Long COVID in Brazilian adults participating in the CUME Study. Methods The CUME Study is a prospective cohort conducted with graduates from federal universities in the State of Minas Gerais, Brazil. In this study, 390 participants who answered the baseline questionnaire in 2016 and the third follow-up questionnaire in 2022 (which contained a block of questions about occurrence of COVID-19 and Long COVID) were included. The diagnosis of Long COVID was based on self-reporting of persistence of signs and symptoms of COVID-19 between 30 days and 6 months after remission of the disease. To estimate the risk and protective factors for Long COVID, a hierarchical multivariate statistical analysis was conducted using the Poisson regression technique. Results Long COVID was observed in 48.9% of the participants. The following characteristics were identified as risk factors for the outcome: female sex (RR = 1.56; 95% CI = 1.22–1.99); prior diagnosis of hypertension (RR = 1.46; 95% CI = 1.19–1.80); having contracted COVID-19 in the first (RR =1.38; 95% CI = 1.07–1.79) or in the second waves (RR = 1.33; 95% CI = 1.07–1.65) of the pandemic period; and having presented three or more signs and symptoms during the acute phase of COVID-19 (RR = 2.99; 95% CI = 1.08–8.24). On the other hand, having a doctoral/postdoctoral educational level (RR = 0.69; 95% CI = 0.50–0.94) was identified as a protective factor for the outcome. Conclusion Health system managers and healthcare professionals should be aware of the socioeconomic profile and disease history of patients who have had COVID-19 because women, people with a prior diagnosis of hypertension, and those who manifested multiple signs and symptoms of COVID-19 during the acute phase of the disease were at greater risk of developing Long COVID.